Structural autonomy and management performance: An influence reinforced in the particular context of portuguese public secondary schools - Carla Fontes; Joaquim Leite; Paula Odete Fernandes (Administrative Sciences, 2022)
The purpose of this research is to verify interdependencies among service innovation, structural autonomy, performance measurement systems, and organizational outcomes in a new organizational context. The relationships between these variables that structure organizational design have been studied for several decades, but it is necessary to verify the validity of those interdependencies in new geographical contexts and periods. Contingency theory was the selected framework because it argues how different scenarios can justify different organizational solutions and is appropriate in the predominant quantitative research. For data collection, surveys were sent to 526 executive heads of all Portuguese public secondary schools, obtaining 154 valid responses. Data processing was carried out using descriptive analysis, Spearman correlation, and structural equation analysis. The results reinforce previous literature, proving the influence of structural autonomy, not only on pedagogical management performance but also on resource management performance within a specific context explored for the first time in the Portuguese public sector. However, the interdependence of these variables in relation to pedagogical innovation strategy and organizational outcomes of effectiveness and efficiency was not verified in this particular setting, corroborating the basic foundations of contingency theory.
Keywords: 350; contingency theory; pedagogical management performance; Portuguese public secondary schools; resource management performance; structural autonomy